The Effectiveness of Mobile Assisted Language Learning (MALL) in Improving Vocabulary Mastery - Linda Tiwi Diarni; Ahmad Faruk (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
The study entitled